2017
DOI: 10.1186/s40337-017-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year follow-up study of completers versus dropouts following treatment with an integrated cognitive-behavioral group therapy for eating disorders

Abstract: BackgroundCognitive-behavioral therapy (CBT) has been recommended for the treatment of eating disorders, and group therapy is known to have certain advantages over individual therapy. The aim of the current study was to compare the 10-year prognosis of patients who completed integrated group CBT with those who dropped out and to examine the effect of completion of group CBT on the prognosis.MethodsThe participants were 65 adult patients with eating disorders. All patients were women and Japanese. The average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Assertiveness training was included as authors noticed that Japanese individuals with ED were not assertive (Okamoto et al, 2017;Shiina et al, 2005); addition of make-up technique session (Kong, 2005).…”
Section: Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Assertiveness training was included as authors noticed that Japanese individuals with ED were not assertive (Okamoto et al, 2017;Shiina et al, 2005); addition of make-up technique session (Kong, 2005).…”
Section: Contentmentioning
confidence: 99%
“…Adapting individual treatments to group treatments. This is due to the lack of specialist treatment centres and trained personnel, yet the demand was high (Okamoto et al, 2017); It was less costly to patients given the healthcare system was not free (Gu et al, 2021;Okamoto et al, 2017); Group treatments can help build confidence and for Japanese individuals to feel less guilty about having an ED (Okamoto et al, 2017) Use of lower intensity treatments (e.g., guided self-help) to increase access due to the lack of specialized services in the community (Setsu et al, 2018); Shortening of treatment to 10 sessions (e.g., Shiina et al, 2005) to make treatment more affordable and acceptable, as some people lived far away (Gu et al, 2021) Theoretical framework Use of the Formative Method for Adapting Psychotherapy (FMAP) when culturally adapting treatment (Hamatani et al, 2022, b) lack of specialist treatment centres, so that trained clinicians could see more patients (Okamoto et al, 2017). Another reason for shortening treatments, was to make them more affordable, as most healthcare systems described were not free and people lived far away from any specialist centres (Gu et al, 2021).…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Peterson et al [30] reported that stress reactivity appears to be especially important for understanding EDs. We previously reported that patients with EDs showed that depressive symptoms and stress coping were improved following treatment [31]. However, there are few studies showing the relationship between subthreshold EDs and stress coping.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions for depression are important because individuals with eating disorders are often suicidal. In addition, we previously reported on the relationships between eating disorders, depressive symptoms and stress coping, and the results showed improvements following treatment [ 23 , 24 ]. We hypothesized that partial symptoms of bulimia would appear early and would be related to depressive symptoms; in addition, this tendency would be noticeable in female students.…”
Section: Introductionmentioning
confidence: 99%